Ներսես Դ Կլայեցի կաթողիկոսի «Շնորհալի» պատվանվան մասին - Շիրինյան, Էռնա Մանեա
The article deals with the honorary title “Graceful” of the 68th Catholicos of Armenians, Nersēs IV Klayets‘i. Such nicknames and honorifics provide interesting data, which is worthy of study. Like the few other famous authors who bore the same epithet: Sargis Shnorhali, Grigor III Pahlavuni, Ignatios of the Black Mountain etc. Nersēs the Graceful was one of the pupils of the renowned didaskalos Step‘anos Manuk. The great pedagogue taught at the monasteries of the Black Mountain (mainly at the monastery called Karmir vank‘), which at that time was a centre of learning with broad scope. Special attention is paid to new understanding of the honorary title “Graceful” (Շնորհալի): that is, its connotation relating to the mouth. After lengthy examination it is concluded that this title could be referring to a person, who is an excellent rhetorician, teacher and exegete. An attempt at connecting it with two other terms, which are also titles, “Chrysostom” (Ոսկեբերան), and “with golden belly” (Ոսկեփորիկ), is made here as well. В статье обсуждается титул «Благодатный», в данном случае определяющий 68-го Католикоса армян – Нерсеса IV Клайеци. Титулы предоставляют весьма интересные данные, относящиеся к различным областям, и достойны изучения. Нерсес Шнорали был одним из учеников, носивших этот же титул (Саргис Шнорали, Григор III Пахлавуни, Игнатий Черногорец и др.) известного дидаскала Степаноса Манука, преподававшего в монастырях Черной горы (главным образом в монастыре Кармир Ванк), которые в то время были центром образования – своего рода международным университетом. Особое внимание уделено новому пониманию титула «Благодатный» (Շնորհալի): а именно, что одну из основных интерпретаций слова должно отнести к «устам», представляющим собой специальный богословский термин. Делается вывод, что этот титул может быть отнесен и к человеку, являющемуся прекрасным ритором, учителем и комментатором. Здесь же предпринята попытка связать его с двумя другими выражениями, также титулами «Златоуст» (Ոսկեբերան) и «Златочрев» (Ոսկեփորիկ).
Keywords: Հայոց եկեղեցու գործիչներ; Պատվանուն